Manajemen Punishment dalam Lembaga Pendidikan Islam - Muhammad Fauzi (Journal on Education, 2023)
An attitude of discipline and a sense of responsibility in the learning process is very necessary, so a method or preventive action is needed, one of these methods is arranging a punishment or punishment in the educational unit which aims to accompany the learning process in order to achieve the expected educational goals. This scientific research is a descriptive qualitative method with a phenomenological research approach. The results of this research are that the aim of punishment in Islamic educational institutions is not to impose negative values ​​on students, but rather to provide punishment using a reward method in tandem with the aim of providing learning so that the value of discipline is a key principle for achieving success in the future. which is in accordance with Islamic principles and values.